Book Review - Kesavan, Varun (International Journal For Research In Business, Management And Accounting, 2021)
The book digital thinking and mobile teaching is one of the most exploring books. The book has emphasized on diverse aspects of mobile based learning which are being incorporated by enormous number of universities with citing the most real practical examples. In the light of present day context the book has explored and it has been segregated into various modules the first phase highlights about the significance of mobile devices, advantages and concepts related to mobile based learning. The book also throws light towards the significance of mobile based teaching process which empowers the teachers to frame and decide their respective course materials including the pedagogy to be adopted by teachers in order to make class sessions more interactive and active learning environment to achieve the utmost satisfaction. The next phase really emphasizes on concept of experience learning equipping the students to develop problem solving skill involving high order thinking and critical thinking modules, also it has also focused on divergent aspects of assessment. On the whole the author has conveyed and has articulated enormous ways of mobile based learning process in a structured and systematic manner by adopting these techniques the learning can be made more interactive and understandable in nature with fullest participation of students during the entire course of action. Even these kinds of strategies can be extended to empower and enhance the standards and quality of students pertaining to other nations. Through this rigorous process the developing nations will be able to enhance the income and standards of living of its countrymen and also upcoming students by adopting innovative techniques like mobile based learning in the arena of education field.